(3TQM dGejI GdYQHs - (3eDjO Hf YHO Gddg GdWja Hf SYjO GdfNOhGfis; (3GdTfaQj Hf GdGhS Hf GdMLQs
(3ChdgG (B:s
(3MOKfG YeGQI Hf Ybjd bGd cGf GdTfaQi Hf eGdc QLdkG ef GdCRO s
(3BNQgG (B:s
(3hcCf heG YedJ ajg ai ehVY JUH Ydi GdMGd ef GdHGA ai Mhdi JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B2 (3U` (B1539 (3Cf dGejI GdYQH gi deDdagG GdSfaQis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B- (3NRGfI Bd HGTf CYjGf GdHUQI (B(26 (3C(B) s
Keywords: (3GdeLGejYs